The Economic Lot Scheduling Problem (ELSP): Review and Extensions - Elmaghraby, Salah E. (Management Science, 1978)
The ELSP is a time-honored problem that “has been around” since 1915. It is the problem of accommodating cyclical production patterns when several products are made on a single facility. Recent contributions to its resolution resulted in either analytical approaches to a restricted problem, or heuristic approaches to the entire problem. This paper reviews critically the various contributions to the problem, and extends the analysis in the following four directions: An improved analytical approach A test for feasibility, A systematic means for escape from infeasibility, and A procedure for the determination of a basic period for a given set of multipliers to achieve a feasible schedule.